Aerobic-exercise training effects on immunological markers in individuals on highly active antiretroviral therapy in Uganda - Constance Adron Nakayiza Nsibambi; Mshilla Maghanga; Edward Ojuka; Mwebaze Nicholas (Turkish Journal of Kinesiology)
There is critical relevance in understanding the multidisciplinary management of HIV/AIDs among individuals obtaining health services in Uganda. The purpose of the study was therefore to assess the effects of aerobic exercise training on immunological markers as a clinical outcome of Human Immunodeficiency Virus positive clients attending a chronic HIV clinic at a General Military Hospital-Bombo. A pre-post experimental design was used to understand differences between the experimental and control groups. Participants were Human Immunodeficiency Virus positive clients who had been on treatment that is, Highly Active Antiretroviral Therapy for at least 12 months. They were randomly assigned to either a control group (Group 1): who did not participate in the aerobic exercise, or an experimental group (Group 2): where a 12-week moderate intensity aerobic exercise, for not less than 3 times a week, and for at least 45 minutes per session was administered. Both groups were assessed using a physical activity readiness questionnaire. Thereafter, assessment of the clinical outcomes that is, immunological measures using Clusters of differentiation 4 were assessed. While the experimental group participated in the exercise, the control group members were followed up during the 12 weeks to ensure that they remained in the study. After the 12 weeks post-test was done. The findings of this study revealed that aerobic exercises significantly increased Clusters of differentiation 4 count in both males and females by 29.7% on average (p